Avaliação dos resultados das contagens de células somáticas obtidas pelo equipamento Ekomilk Scan e suas correlações com outros métodos de análise - Gonçalves, Ana Carolina Siqueira [UNESP] (2014)
The advent of alternative methods for SCC becomes useful tool for producers to monitor the health of the mammary gland and also the livestock. The present study aimed to evaluate the equipment Ekomilk Scan® as an alternative to somatic cell count in milk, testing their effectiveness and reliability as well as compare it to the standard and reference methods. For this were collected individual cow milk samples of various ages and different stages of lactation in northeastern state of São Paulo region. Variables inherent to the equipment (repeatability and reproducibility), and those that are merely influencing the outcome (use of preservative, temperature, time between collection and analysis, breed and milk composition) were tested. The dependent variables were analyzed using the SAS System and the test of least squares. The results indicated that the Ekomilk Scan® is precise and presents concise results when performed independently but under the same conditions. To perform the samples should not add preservative and the analyses should be conducted on the same day of collection despite the temperature at which the sample is not significantly influence the results. Furthermore, when comparing the Ekomilk Scan® to other methods of analysis, that the results showed good correlation with the optical microscope method. Thus, it is concluded that the equipment tested is accurate and reliable and may be a good alternative for monitoring of SCC in production units